Behavioral Abnormalities in a Mouse Model of Chronic Toxoplasmosis Are Associated with MAG1 Antibody Levels and Cyst Burden. - Jianchun Xiao; Ye Li; Emese Prandovszky; Geetha Kannan; Raphael P Viscidi; Mikhail V Pletnikov; Robert H Yolken (Public Library of Science (PLoS), 2016)
There is marked variation in the human response to Toxoplasma gondii infection. Epidemiological studies indicate associations between strain virulence and severity of toxoplasmosis. Animal studies on the pathogenic effect of chronic infection focused on relatively avirulent strains (e.g. type II) because they can easily establish latent infections in mice, defined by the presence of bradyzoite-containing cysts. To provide insight into virulent strain-related severity of human toxoplasmosis, we established a chronic model of the virulent type I strain using outbred mice. We found that type I-exposed mice displayed variable outcomes ranging from aborted to severe infections. According to antibody profiles, we found that most of mice generated antibodies against T. gondii organism but varied greatly in the production of antibodies against matrix antigen MAG1. There was a strong correlation between MAG1 antibody level and brain cyst burden in chronically infected mice (r = 0.82, p = 0.0021). We found that mice with high MAG1 antibody level displayed lower weight, behavioral changes, altered levels of gene expression and immune activation. The most striking change in behavior we discovered was a blunted response to amphetamine-trigged locomotor activity. The extent of most changes was directly correlated with levels of MAG1 antibody. These changes were not found in mice with less cyst burden or mice that were acutely but not chronically infected. Our finding highlights the critical role of cyst burden in a range of disease severity during chronic infection, the predictive value of MAG1 antibody level to brain cyst burden and to changes in behavior or other pathology in chronically infected mice. Our finding may have important implications for understanding the heterogeneous effects of T. gondii infections in human.